Análise do comportamento de sistemas estruturais em concreto moldado in loco sob o efeito do colapso progressivo - Ruthes, Heloiza Candeia (2020)
This work aims to investigate the behavior of cast-in-place reinforced concrete structures in the ultimate limit state of collapse. Progressive collapse is the disproportionate spread of a local failure due to the incidence of exceptional loads, such as an explosion, earthquakes, vehicle impact and fire. However, the information contained in the Brazilian Standard is not sufficient to help the designer include checking the progressive collapse in the design and design of structures. Thus, the objective of this work is to propose a classification of structures according to the need to consider the progressive collapse and, subsequently, to analyze the behavior of a model building in reinforced concrete, with several storeys, in the event of failure or loss of columns, simulating the situation of progressive collapse, with the application of conventional methods contained in international standards and documents, compare the application of known methods, as well as analyze the redistribution of internal stresses in the elements adjacent to the column removed in each case. For this, four analytical models of a five-storey building were simulated, before the application of different methods of prevention and verification regarding progressive collapse, in the SAP 2000® software, for four different cases, in which external pillars are removed. After the initial phase of the research, through other existing international classifications, a classification table of conventional structures was proposed according to their occupation and, for each group, a method to be used for this consideration was recommended. Regarding the results of the structure analysis, the results for bending moment, axial load and nodal displacements diagrams caused in the structure after the loss of the vertical element were obtained. After the initial phase, the results obtained were analyzed and it was found that the alternative path method proved to be more effective for the analyzed structure.